(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Colonial sufferings and trauma of Mathinna are predominantly prevailed in any studies on Richard Flanagan’s Wanting. It is very hard to know about feministic approaches on the character of Lady Jane Franklin. This research article focuses on imperial maternalism from postcolonial feminism to reveal such unsung character who is longing for cultural control. Imperial maternalism is a concept developed in postcolonial feminist studies which is used to control the colonial domination by a mother’s role of care and language. By looking at Lady Franklin’s adoption of Mathinna, her public grief, and her influence inside a male-dominated colonial world, the paper shows how a woman’s power can work and also be limited under empire.